SYSTEMATIC LITERATURE REVIEW ON CREATIVITY IN THE FIELD OF SCIENCE LEARNING: DOMAIN, RESEARCH TRENDS, AND THEIR ANALYSIS - Sigit Sujatmika; Endang Sri Lestari; Harry Affandy (EDUSAINS, 2022)
SYSTEMATIC LITERATURE REVIEW PADA KREATIVITAS BIDANG PEMBELAJARAN SAINS: DOMAIN, TREND PENELITIAN, DAN ANALISISNYAAbstractCreativity is an important aspect to be developed in students and becomes one of the main skills needed in the world of work. This study aims to review the results of research on creativity in the field of science education which includes aspects of domains, research trends, and methods. Systematic Literature Review (SLR) is carried out carefully and strictly on articles sourced from international reputable databases. The selection results obtained 22 articles published from 2010 to 2020. The perspective of creativity research lies in the 4Ps (Person, Process, Product, and Press) as a single component. The trend of creativity research is mostly related to multi-representation, concept understanding, evaluation, and creative learning design. In addition, research trends are explored to improve the creative processes and products of junior high and high school students, as well as several course institutions and elementary schools. While the most creative research methods use quasi-experimental and mixed methods. Research with a quasi-experimental design allows the measurement process before and after treatment. Researchers can find out whether the treatment has an effect on creativity in terms of the results of statistical tests.AbstrakKreativitas merupakan aspek penting untuk dikembangkan pada siswa dan menjadi salah satu keterampilan utama yang dibutuhkan di dunia kerja. Kajian ini bertujuan untuk mereview hasil penelitian-penelitian tentang kreativitas bidang pendidikan sains yang meliputi aspek domain, trend penelitian, dan analisisnya. SLR dilakukan pada artikel-artikel yang bersumber dari database bereputasi internasional. Hasil seleksi diperoleh 22 artikel yang diterbitkan dalam rentang 2010 sampai 2020. Sudut pandang penelitian kreativitas terletak pada 4P (Person, Process, Product, dan Press) sebagai sebuah komponen satu kesatuan. Tren penelitian kreativitas paling banyak berkaitan dengan multirepresentasi, pemahaman konsep, evaluasi, dan desain pembelajaran kreativitas. Selain itu, trend penelitian melakukan eksplorasi untuk meningkatkan proses dan produk kreativitas siswa sekolah menengah pertama dan sekolah menengah atas, juga beberapa lembaga kursus dan sekolah dasar. Sedangkan teknik analisis data  penelitian kreativitas paling banyak menggunakan quasi eksperimen dan metode campuran. Penelitian dengan desain quasi-eksperimental memungkinkan proses pengukuran sebelum dan sesudah treatment sehingga peneliti dapat mengetahui apakah perlakukan yang diberikan berpengaruh terhadap kreativitas berdasarkan hasil uji statistik. How To Cite: Sujatmika, S., Lestari, E.S., Affandy, H. (2022). Systematic Literature Review Pada Kreativitas Bidang Pembelajaran Sains: Domain, Trend Penelitian, dan Analisisnya. EDUSAINS, 14 (1) : 34-49.